Correcting North Atlantic Sea Surface Salinity Biases in the Kiel Climate Model: Influences on Ocean Circulation and Atlantic Multidecadal Variability - Park, Taewook; Park, Wonsun; Latif, Mojib (Climate Dynamics, 2016)
A long-standing problem in climate models is the large sea surface salinity (SSS) biases in the North Atlantic. In this study, we describe the influences of correcting these SSS biases on the circulation of the North Atlantic as well as on North Atlantic sector mean climate and decadal to multidecadal variability. We performed integrations of the Kiel Climate Model (KCM) with and without applying a freshwater flux correction over the North Atlantic. The quality of simulating the mean circulation of the North Atlantic Ocean, North Atlantic sector mean climate and decadal variability is greatly enhanced in the freshwater flux-corrected integration which, by definition, depicts relatively small North Atlantic SSS biases. In particular, a large reduction in the North Atlantic cold sea surface temperature bias is observed and a more realistic Atlantic Multidecadal Variability simulated. Improvements relative to the non-flux corrected integration also comprise a more realistic representation of deep convection sites, sea ice, gyre circulation and Atlantic Meridional Overturning Circulation. The results suggest that simulations of North Atlantic sector mean climate and decadal variability could strongly benefit from alleviating sea surface salinity biases in the North Atlantic, which may enhance the skill of decadal predictions in that region.